Evaluasi Tingkat Status Gizi Pada Balita di Wilayah Kerja Puskesmas Kamonji Kota Palu - Fitri Arni HR; Sri Purwiningsih; Desak Eka Susianawati (Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2022)
Fulfillment of nutrition in children under five years of age is a factor that needs to be considered in maintaining health because toddlerhood is a period of development that is vulnerable to nutrition. Malnutrition is a lack of nutrients such as protein, carbohydrates, fats, and vitamins needed by the body. The case of death that occurs in children under five is one of the consequences of poor nutrition. Service activities have been carried out from October 2 to 28, 2021 for parents of toddlers in the Kamonji Health Center area of ​​Palu City. In the implementation of service activities, parents have a very high curiosity about balanced nutritional needs and understand how to modify food, modify family recipes to increase toddlers' appetite, and practice healthy food processing methods for toddlers. Providing information through education and training aims to increase knowledge, then it will raise awareness and in the end someone will practice it according to the knowledge he has.